From Adaptation to Appropriation? Exploring the Legacy of Ruth Stiles Gannett’s Novel in Masami Hata’s Elmer No Boken and Nora Twomey’s My Father’s Dragon - Louckx, Audrey (Transcr(é)ation)

(untitled) (Western Libraries, University of Western Ontario, 2025)
Ruth Stiles Gannett’s début novel, My Father's Dragon (1948), has inspired many generations of children worldwide. This inspiration was so significant that it gave way to an animated adaptation in 1997 by Japanese director Masami Hata. Elmer no Boken offers a relatively faithful adaptation of the novel’s narrative. However, its aesthetic is resolutely transcultural as it shows inspiration from the original lavish grease crayon illustrations while imbuing them with some of the typical techniques of anime films. In 2022, Netflix released a new adaptation driven by five-time nominated Oscar Irish studio Cartoon Saloon. My Father’s Dragon beautifully displays the studio’s trademark reliance on “clean geometric shapes against stylized backgrounds” (Zahed, 2022, p. 26), in which director Nora Twomey presents stylized yet recognizable representations of Elmer and the dragon.However, this new adaptation gives the audience a transformed version of the adventure that eventually brings together these two young children figures who learn to trust in their own and each other’s capacities. Using Paul Wells’s model of animated adaptations as subjective correlatives of their initial literary sources, this paper will seek to compare both adaptations to emphasize how the directors’ style and the studios’ aesthetic have come to support what appears to be radically different interpretations of the source material. As Sanders puts it, all adaptations seek to solve an “equation” (2016, p.17), that of a tension between the old and the new. In this respect, Hata’s and Twomey’s films may well display an inescapable movement from adaptation to appropriation.